Peran Memorable Tourism Experience Terhadap Kepuasan Wisatawan di Museum Prabu Geusan Ulun - Mariyana Kusuma Fauziyyah; Gilang Pratama Putra; Tedi Supriadi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Prabu Geusan Ulun Museum is an educational tourism that can provide cultural information and a place to store historical heirlooms, despite having low number tourist visits. To increase the number of tourist visits, it is necessary to understand what visitors need in increasing the existence of Prabu Geusan Ulun Museum. Memorable tourism experience is an important agenda in the purpose of this research, considering that tourism is basically based on experience that has an influence on determining tourist satisfaction. Tourist satisfaction is felt when the expectations of tourists are met. The methods used in this research was quantitative method with survey as the research design. Questionairres were used to collect data from 100 respondents using non-probability sampling technique and descriptive data analysis. The finding showed that there was a significant influence of memorable tourism experience (X) on tourist satisfaction (Y) with a value of 0,001<0,05. The result of the hypothesis test of > was 14.705 > 1.984, therefore Ha was accepted. The findings of this research may help create a marketing strategy for Prabu Geusan Ulun Museum by using memorable tourism experience dimension which will later increase the number of tourist visits to Prabu Geusan Ulun Museum.